2020
DOI: 10.3390/ijerph17010331
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Regularity Index in Patients with Alcohol Dependence: Daytime Napping and Mood Disorders as Correlates of Interest

Abstract: Alcohol use disorder (AUD) is often accompanied by comorbid conditions, including sleep disturbances related to sleep regularity and timing. The Sleep Regularity Index (SRI) is a novel measure that assesses the probability that an individual is awake (vs. asleep) at any two time points 24 h apart. We calculated actigraphy-based SRI on 124 participants with alcohol dependence to capture the effects of changes in sleep timing and duration among patients enrolled in an inpatient alcohol treatment program. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
2
12
1
Order By: Relevance
“…Alcohol is known to alter sleep and regularity. Alcohol intoxication may lead to a shorter sleep onset latency but poorer sleep quality in the latter part of the sleep, resulting in shorter sleep duration and sleep disruption; in addition, irregularity in sleep-wake schedules are associated with a higher risk of alcohol use [ 46 , 47 ]. The present study shows that alcohol consumption among students is indirectly associated with proper sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol is known to alter sleep and regularity. Alcohol intoxication may lead to a shorter sleep onset latency but poorer sleep quality in the latter part of the sleep, resulting in shorter sleep duration and sleep disruption; in addition, irregularity in sleep-wake schedules are associated with a higher risk of alcohol use [ 46 , 47 ]. The present study shows that alcohol consumption among students is indirectly associated with proper sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found lower SRI to be associated with depression ( Pye et al, 2021 ), insomnia, post traumatic stress disorder (PTSD) ( Mascaro et al, 2021 ), poorer mood ( Sano et al, 2015 ), cardiometabolic dysfunction ( Lunsford-Avery et al, 2018 ; Fritz et al, 2020 ), and poorer functional outcomes in autism ( Cohen et al, 2017 ) and delayed sleep-wake phase disorder ( Murray et al, 2019 ). The SRI has also been found to improve with treatment for alcohol dependence ( Brooks et al, 2020 ). Our findings show that SRI is also a strong predictor for measures of QoL in cancer populations, including both functional and symptom scores.…”
Section: Discussionmentioning
confidence: 99%
“…Although the physiological and biological mechanisms common to depression and circadian rhythms are unclear (41), approximately 50-90% of MDD patients reported complaints about impairment of sleep quality (42). Recently, a study found that the average sleep regulatory index (measure that assesses the probability that an individual is awake) in persons without bipolar/depression disorder is higher than in those with such disorders (43). It has been suggested that MDD patients can recover from their depression by successfully handling their insomnia (44).…”
Section: Introductionmentioning
confidence: 99%